Good student-athlete representation - Vicki Schull; Lisa A. Kihl (Journal of Intercollegiate Sport, 2024)
The current landscapes of intercollegiate sports and higher education are experiencing shifts toward more democratic representation. In college sport, student-athlete representatives are more engaged in policy decisions, hold voting rights, and are included on boards and committees. Despite this shift, little is known about what good intercollegiate athlete representation entails and how multi-level, democratic governance systems may support or impede good representation in the context of college sport. This paper explores qualities of good college athlete representation (CARep) and factors contributing to and/or detracting from the process of good CARep in the context of a democratic multi-level intercollegiate sport governance system. Findings showed individual attributes of good CARep, including interpersonal skills and leadership, were based on democratic representation virtues (i.e., fairmindedness, trust building, good gatekeeping) and helped foster democratic values of civic equality, self-governance, and inclusion. The intercollegiate sport governance system supports the work of athlete representatives primarily through its educative function. More specifically, administrators were key to identifying experiential learning opportunities for athlete representatives, which contributed to the process of good representation through responsiveness, inclusiveness, and egalitarianism. Lack of administrative support and education for all relevant interest groups characterized governance system inconsistencies impeding good CARep, primarily at institutional levels where the purpose of student-athlete committees varied and/or athlete representative roles were less understood. Implications for practice and directions for future research on good athlete representation are presented.